Kreasi Cetak Sablon Mudah dan Berkualitas Tinggi pada Kaos - Luzar, Laura Christina (Humaniora, 2010)
Silk screen printing is the most demanding printing until now. Besides the processing was easy and simple, this printing technique is easy to be understood in a relatively short time. The most important thing in silk screen printing is perseverance, accuration, and creativity. By the relatively low cost, could begin to learn silk screen printing technique.The processing of silk screen printing can be done manually, with a drop of equipment. Starting from the process of image planning, copy process, until the printing process, all of these phases could be done without the support of developing technologies. However it can not be denied that the rapidly developing technologies make the work easier.